2018
DOI: 10.1097/ccm.0000000000003023
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Acute Organ Dysfunction on Long-Term Survival in Sepsis*

Abstract: Acute sepsis-related neurologic dysfunction was the organ dysfunction most strongly associated with short- and long-term mortality and represents a key mediator of long-term adverse outcomes following sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 42 publications
5
89
2
5
Order By: Relevance
“…Research on more restricted patient populations in the ED, suspected infection or sepsis patients, has presented in-hospital mortality around 10%, 30-day mortality between 10% and 25% and 1-year mortality around 30%, and in parallel to the present study with mortality increasing by increasing number of organ failures 4 42 43. Furthermore, cerebral failure, as in our study, had the strongest association with short-term mortality, followed by respiratory and circulatory failure, the latter in contrast to our study, and hepatic and cerebral failure were associated with long-term mortality 14. In organ failure patients with positive blood culture, the highest in-hospital mortality was observed in patients with circulatory failure followed by respiratory and cerebral 15.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Research on more restricted patient populations in the ED, suspected infection or sepsis patients, has presented in-hospital mortality around 10%, 30-day mortality between 10% and 25% and 1-year mortality around 30%, and in parallel to the present study with mortality increasing by increasing number of organ failures 4 42 43. Furthermore, cerebral failure, as in our study, had the strongest association with short-term mortality, followed by respiratory and circulatory failure, the latter in contrast to our study, and hepatic and cerebral failure were associated with long-term mortality 14. In organ failure patients with positive blood culture, the highest in-hospital mortality was observed in patients with circulatory failure followed by respiratory and cerebral 15.…”
Section: Discussionsupporting
confidence: 83%
“…Organ failure was defined based on Sequential Organ Failure Assessment (SOFA) Score,24 25 which is used in the intensive care unit (ICU) setting. Due to research located in an ED, we used modified definitions that were based on SOFA criteria and with input from quick-SOFA (qSOFA)14 26–30:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, sepsis-associated encephalopathy (SAE) is one of the most common etiological factors for febrile encephalopathy, especially in elderly people. Approximately 70% of patients with bacteremia develop neurological symptoms ranging from lethargy to coma, and over 80% suffer from abnormalities as measured by electroencephalogram (EEG) [3,4]. Moreover, it has been identified that SAE is critically involved in increased mortality, extensive in-hospital cost, and prolonged hospitalization, followed by persistent cognitive impairment and limitations in physical function [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The constant interest in sepsis research is justified by data showing an increased number of deaths despite a reduction in sepsis-associated mortality during the last four decades; the intra-hospital risk of death by sepsis is 10-20%, and increases to 40-80% in septic shock [1][2][3][4]. Sepsis associated mortality became higher due to the increased rates of diagnosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%